High-conductivity polymer transmission layer material and preparation method thereof

By grafting polycomponent fused-ring aromatic hydrocarbons or their derivatives on the molecular side chains of imine polymers, a highly conductive polymer transport layer material is prepared, which solves the problem of low conductivity of existing conductive polymer materials and significantly improves the photoelectric conversion efficiency and stability of OSCs devices.

CN119859260APending Publication Date: 2025-04-22TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510072512.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing conductive polymer materials for organic solar cells (OSCs) have low conductivity, limiting the charge transfer capability of the electron transport layer and the photoelectric conversion efficiency of the device.

Method used

Highly conductive polymer transport layer materials are prepared by grafting polycomponent fused-cyclic aromatic hydrocarbons or derivatives on the molecular side chains of imine polymers. This material is prepared in an alcohol solution by solvothermal reaction, forming an ETL material with excellent electrical properties and high electron mobility.

Benefits of technology

The electron mobility of the electron transport layer is significantly improved, the photoelectric conversion efficiency of the OSCs device is enhanced, the preparation cost is reduced, and the ultraviolet stability and air stability of the device are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859260A_ABST
    Figure CN119859260A_ABST
Patent Text Reader

Abstract

The invention relates to a high-conductivity polymer transport layer material, which is formed by grafting polybasic polycyclic aromatic hydrocarbon or derivatives thereof on a molecular side chain of an imine polymer serving as a matrix material through solvothermal reaction, and can be directly spin-coated on a conductive substrate and annealed to form an ETL layer. The high-conductivity polymer transmission layer material has excellent electrical properties, solves the problem of conductivity of the material when being used for preparing OSCs, has better compatibility with an organic active layer, reduces interface defects, improves the charge extraction and transmission capability of OSCs devices, and shows higher ultraviolet stability and air stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optoelectronic functional materials and devices, and relates to a transport layer material, and in particular to a transport layer material with high conductivity. The transport layer material of the present invention is suitable for use as an electron transport layer (ETL) material of organic solar cells (OSCs) and other optoelectronic devices. Background Art

[0002] Organic solar cells (OSCs) have attracted extensive attention from researchers due to their advantages such as light weight, good flexibility, and roll-to-roll production. With the emergence of new active layer materials and interface materials, the photoelectric conversion efficiency (PCE) of rigid single-section OSCs has exceeded 20% (Non-fullerene acceptor with asymmetric structure and phenyl-substituted alkyl side chain for 20.2% efficiency organic solar cells, Nature Energy , 2024, 9, 975-986.), the highest PCE of flexible OSCs also reached 18.3% (20.2% Efficiencyorganic photovoltaics employing a π-extension quinoxaline-based acceptor withordered arrangement, Advanced Materials , 2024, 36(33), 2406690.).

[0003] The electron transport layer (ETL) materials of OSCs play a key role in achieving the high efficiency and long-term stability of the device. First, the ETL material must form an efficient electron transport channel to improve the electron transport and transport capabilities, which is the basis for achieving high device efficiency; secondly, the ETL material also needs to meet the conditions of low-temperature solution processability as much as possible to reduce the energy consumption and cycle cost during device preparation.

[0004] Commonly used ETL materials mainly include inorganic metal oxides, organic polymers and small molecule materials. Among them, inorganic metal oxides (ZnO, TiO2, SnO2, etc.) have high electron mobility, chemical stability and energy level matching, but their preparation requires high temperature conditions, and the roughness of the prepared film is high, which affects the quality of the light absorption layer (An overview of electron transport layer materials and structures for efficient organic photovoltaic cells, Energy Technology , 2024, 12, 2400285.); organic polymers and small molecule materials (PDINN, PFN, C 60 It has the advantages of low cost, flexibility, light weight and good interface optimization, but has the disadvantages of poor conductivity, poor stability and high processing requirements (An overview of electron transport layermaterials and structures for efficient organic photovoltaic cells, Energy Technology , 2024, 12, 2400285.).

[0005] A class of conductive polymers composed of conjugated skeletons and polar side chains, with good electrode work function modification ability and excellent alcohol solubility, including PFN-Br, PEI, PEIE, etc., can be used to prepare multilayer devices through orthogonal processing. The representative alcohol-soluble conductive polymer material is PEI, which can form a strong electrostatic self-assembled dipole of protonated amine at the cathode interface, thereby reducing the work function of ITO and adapting its energy level to the active layer. In addition, the energy level of PEI itself can also be adjusted by chemical modification to achieve better energy level matching with various active layers, improve the transmission efficiency of electrons between ETL and adjacent layers, and reduce the energy loss caused by band mismatch. In addition, PEI also has high light transmittance, good solubility and processability, and low cost, and is an excellent OSCs cathode interface material.

[0006] However, the application of PEI is greatly affected due to its low electron mobility and its optimal working thickness of only a few nanometers.

[0007] Therefore, the modification of PEI with other materials to improve its conductivity has attracted the attention of researchers. Nie et al. (High-Performance inverted organic solar cells via the incorporation of thickness-insensitive and low-temperature-annealed nonconjugated polymers aselectron transport materials, ACS Applied Materials & Interfaces , 2023, 15, 1718-1725.) Glycerol diglyceride ether (GDE) and 1,4-butane sulfonic acid (BS) were blended with PEI to prepare cross-linked PEI-based materials PEI-GDE and PEI-GDE-BS, which can be used to replace traditional ZnO materials in inverted OSCs. The PCE of the PEI-GDE-BS device was 17.55%, V OC is 0.83V, J SC 27.88 mA / cm 2 , FF is 75.96%.

[0008] Dong et al. (Revival of insulating polyethylenimine by creativelycarbonizing with perylene into highly crystallized carbon dots as the cathodeinterlayer for high-performance organic solar cells, ACS Applied Materials & Interfaces , 2022, 14, 1280-1289.) Water-soluble carbon dots (CDs) were synthesized as ETLs by a one-step hydrothermal method using 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), a derivative of the condensed aromatic hydrocarbon perylene, and PEI as raw materials. In terms of device photovoltaic performance, the inverted OSCs based on the CDs achieved a PCE of 17.35%. Summary of the invention

[0009] The purpose of the present invention is to provide a highly conductive polymer transport layer material and a preparation method thereof, so as to further improve the charge transfer capability of the electron transport layer and ultimately improve the photoelectric conversion efficiency of the device.

[0010] Polycyclic aromatic hydrocarbons and their derivatives have strong electron donating ability, excellent structural planarity, thermal stability, strong charge transfer ability and other advantages, and can be considered as external molecules to be grafted onto conductive polymers. In view of this, the present invention starts from the aspect of modifying conjugated conductive polymers, and creatively develops a method for grafting polycyclic aromatic hydrocarbons and their derivatives to improve conductivity. The conductive polymer after grafting modification can not only be used as ETL material of OSCs, but also suitable for other optoelectronic devices.

[0011] The highly conductive polymer transport layer material of the present invention is a material that uses an imine polymer as a base material and grafts polycyclic aromatic hydrocarbons or their derivatives onto the molecular side chains through a solvent thermal reaction.

[0012] Among them, the imine polymer not only has excellent electrical conductivity, but also has good water solubility or alcohol solubility, which may include but is not limited to any one of polyethyleneimine (PEI), polyethoxyethyleneimine (PEIE), N,N'-bis{3-[3-(dimethylamino)propylamino]propyl}perylene-3,4,9,10-tetracarboxylic acid diimide (PDINN), or its halogen element substituted derivatives.

[0013] The polycyclic aromatic hydrocarbons or their derivatives may include, but are not limited to, various cyclic aromatic hydrocarbons such as naphthalene, phenanthrene, anthracene, pyrene, and small molecule substituted derivatives with the cyclic aromatic hydrocarbons as the core.

[0014] Furthermore, the small molecule substituted derivatives described in the present invention are preferably carboxylic acid substituted derivatives, including but not limited to 1-naphthoic acid, 2-naphthoic acid, 9-anthracenecarboxylic acid, 1-pyrenecarboxylic acid and other derivatives.

[0015] Furthermore, the highly conductive polymer transport layer material of the present invention is prepared from an imine polymer and a polycyclic aromatic hydrocarbon or a derivative thereof in a mass ratio of (0.2-1):1.

[0016] Furthermore, the present invention also provides a specific preparation method of the highly conductive polymer transport layer material, which comprises dissolving a polycyclic condensed aromatic hydrocarbon or a derivative thereof in an alcohol solvent, adding an alcohol solution of the imine polymer to the polycyclic condensed aromatic hydrocarbon or a derivative thereof at a mass ratio of (0.2 to 1):1, carrying out a solvent thermal reaction at 100 to 200° C. in a sealed container, and directly using the alcohol solution of the reaction product as the ETL material.

[0017] More specifically, the solvent thermal reaction time of the present invention is preferably 10 to 15 hours.

[0018] The highly conductive polymer transport layer material prepared by the present invention has excellent electrical properties. The conductivity of the material formed into a thin film is measured, which is greatly improved compared with the conductivity of the imide polymer matrix material before grafting, indicating that the electron mobility of the material prepared by the present invention is also greatly improved, and it is suitable for application as an ETL material for OSCs.

[0019] Specifically, the ETL material prepared in the present invention is directly spin-coated on a conductive substrate by a conventional preparation method, and an ETL layer can be formed on the surface of the conductive substrate after annealing.

[0020] Furthermore, by spin coating a conventional organic active layer on the ETL layer formed by the present invention, and vacuum evaporating an HTL layer and a metal electrode, an organic solar cell (OSCs) with good conductive properties can be prepared, thereby solving the problem of low conductivity of the existing conductive polymer materials used for OSCs.

[0021] Furthermore, the annealing temperature of the ETL material is preferably 60°C.

[0022] Compared with metal oxide ETL materials such as ZnO commonly used in conventional inverted OSCs, the highly conductive polymer transport layer material described in the present invention has better compatibility with the upper organic active layer, which is manifested in that the interface impedance between the device's electron transport layer and the organic active layer is greatly reduced, indicating that it has better ohmic contact with the upper organic active layer, reduces defects at the interface, and is conducive to achieving good charge transfer and collection at the interface, so that the OSCs device has higher charge extraction and transmission capabilities.

[0023] In addition, in the relevant literature reports, sol-gel ZnO (Toward flexible and stretchable organic solar cells: A comprehensive review of transparent conductive electrodes, photoactive materials, and device performance, Advanced Energy Materials , 2024, 2404233) and nanoparticle ZnO (Synthesis of N,S-Doped carbon quantumdots for use in organic solar cells as the ZnO modifier to eliminate the light-soaking effect, ACSApplied Materials & Interfaces , 2019, 11(2), 2243-2253.) are all at relatively high annealing temperatures, reaching 200°C and 130°C respectively. Compared with these high temperature annealing processes, the annealing temperature required for forming the ETL layer using the highly conductive polymer transport layer material of the present invention is only 60°C, which is more conducive to reducing the preparation cost of OSCs.

[0024] Furthermore, the OSCs device prepared using the highly conductive polymer transport layer material of the present invention also exhibits higher UV stability and air stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is the UV-visible absorption spectrum of the ETL material prepared in Examples 1 to 4 and the raw materials PEI and Pyrene.

[0026] Figure 2 It is the transmittance spectrum of the ETL material prepared in Examples 1 to 4 and the raw materials PEI and Pyrene.

[0027] Figure 3 These are SEM and TEM images of the ETL material prepared in Example 5 and the raw material PEI.

[0028] Figure 4 This is the FTIR spectrum of the ETL material prepared in Example 5 and the raw material PEI.

[0029] Figure 5 This is the XPS spectrum of the ETL material prepared in Example 5 and the raw material PEI.

[0030] Figure 6 The IV curves of different ETL materials are tested using a single electron layer device with the structure of ITO / ETL / Al.

[0031] Figure 7 The OSCs prepared in Example 12 and Comparative Example 1 JV curve.

[0032] Figure 8 EQE curves and integrated current curves of OSCs prepared in Example 12 and Comparative Example 1.

[0033] Fig. 9 1 is the dark current curve of OSCs prepared in Example 12 and Comparative Example 1.

[0034] Fig.10 is the electrochemical impedance spectra of OSCs with different ETL materials.

[0035] Fig.11 It is the air stability curve of OSCs prepared in Example 12 and Comparative Example 1.

[0036] Fig.12It is the UV stability curve of OSCs prepared in Example 12 and Comparative Example 1. Implementation

[0037] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0038] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or conditions recommended by the manufacturer.

[0039] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.

[0040] The ETL material provided in the following embodiments of the present invention is specifically prepared from PEI and polycyclic aromatic hydrocarbons or their derivatives as raw materials, and polycyclic aromatic hydrocarbons or their derivatives are grafted onto the side chains of PEI molecules by a simple one-step solvothermal method in an alcohol solution to obtain a polycyclic aromatic hydrocarbon or its derivative: PEI interface layer material.

[0041] The following embodiments of the present invention also use the ETL material to prepare OSCs, specifically including:

[0042] Providing a conductive substrate, and spin-coating the prepared ETL material solution onto the conductive substrate to form an ETL cathode interface layer on the surface of the conductive substrate;

[0043] Providing an organic active layer solution, and spin-coating the organic active layer solution onto the cathode interface layer, so that an organic active layer is formed on the surface of the cathode interface layer;

[0044] Forming a HTL layer by vacuum evaporation on the surface of the organic active layer;

[0045] And, a metal electrode is formed on the surface of the HTL layer by vacuum evaporation. Example

[0046] Example 1

[0047] Weigh 0.12 g of pyrene, dissolve it in 30 mL of ethanol, and disperse it by ultrasonic for 30 min. Add 3 mL of 8 mg / mL PEI ethanol solution, transfer it to a high-pressure reactor, and heat it to 100 °C for solvothermal reaction for 10 h.

[0048] After the reaction was completed, the mixture was naturally cooled to room temperature, and the reaction solution was taken out to prepare a Pyrene:PEI ethanol solution with a mass ratio of Pyrene to PEI of 1:0.2. The ethanol solution was directly used as the ETL material of OSCs.

[0049] Example 2

[0050] Weigh 0.12 g of pyrene, dissolve it in 30 mL of ethanol, and disperse it ultrasonically for 30 min. Add 7.5 mL of 8 mg / mL PEI ethanol solution, transfer it to a high-pressure reactor, and heat it to 120°C for solvothermal reaction for 10 h.

[0051] After the reaction was completed, the mixture was naturally cooled to room temperature, and the reaction solution was taken out to prepare a Pyrene:PEI ethanol solution with a mass ratio of Pyrene to PEI of 1:0.5. The ethanol solution was directly used as the ETL material of OSCs.

[0052] Example 3

[0053] Weigh 0.12 g of pyrene, dissolve it in 30 mL of ethanol, and disperse it ultrasonically for 30 min. Add 12 mL of 8 mg / mL PEI ethanol solution, transfer it to a high-pressure reactor, and heat it to 150°C for solvothermal reaction for 10 h.

[0054] After the reaction was completed, the mixture was naturally cooled to room temperature, and the reaction solution was taken out to prepare a Pyrene:PEI ethanol solution with a mass ratio of Pyrene to PEI of 1:0.8. The ethanol solution was directly used as the ETL material of OSCs.

[0055] Example 4

[0056] Weigh 0.12 g of pyrene, dissolve it in 30 mL of ethanol, and disperse it by ultrasonic for 30 min. Add 15 mL of 8 mg / mL PEI ethanol solution, transfer it to a high-pressure reactor, and heat it to 200 °C for solvothermal reaction for 10 h.

[0057] After the reaction was completed, the mixture was naturally cooled to room temperature, and the reaction solution was taken out to prepare a Pyrene:PEI ethanol solution with a mass ratio of Pyrene to PEI of 1:1. The ethanol solution was directly used as the ETL material of OSCs.

[0058] Good optical properties are crucial for interface materials used in organic solar cells. Therefore, after the Pyrene:PEI ethanol solutions prepared in the above embodiments were formed into films, the absorption and transmission properties of the films were characterized and compared with those of pure PEI and Pyrene.

[0059] Figure 1 In the UV-visible absorption spectrum, it was observed that both pure Pyrene and Pyrene:PEI film had a strong absorption peak in the 225-250nm region, representing the π-π* transition of the aromatic ring in the pyrene molecule, which is one of the main characteristics of the pyrene molecule. Some weaker absorption peaks were also observed at longer wavelengths of >250nm, representing the absorption of other functional groups in the pyrene molecule.

[0060] In terms of light transmittance, Figure 2 The transmittance curves of PEI, Pyrene and Pyrene:PEI films are shown in Figure 1. Among them, PEI has the highest transmittance as an electron transport layer material, and Pyrene:PEI film also has a high transmittance in the range of 400-1000nm, thus ensuring that the active layer has sufficient light absorption in the near-infrared and visible light regions of the solar spectrum. PEI and Pyrene:PEI have the same transmittance in the visible light region, indicating that Pyrene:PEI, as an electron transport layer material, does not affect the light absorption of the active layer.

[0061] Example 5

[0062] Weigh 0.12 g of 1-pyrenecarboxylic acid (1-PyCA), dissolve it in 30 mL of ethanol, and disperse it by ultrasonic for 30 min. Add 3 mL of 8 mg / mL PEI ethanol solution, transfer it to a high-pressure reactor, and heat it to 100 °C for solvothermal reaction for 15 h.

[0063] After the reaction was completed, the mixture was naturally cooled to room temperature, and the reaction solution was taken out to prepare a 1-PyCA:PEI ethanol solution with a mass ratio of 1-PyCA to PEI of 1:0.2. The ethanol solution was directly used as the ETL material of OSCs.

[0064] To verify and reveal the formation mechanism of 1-PyCA:PEI, 1-PyCA:PEI was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and PEI was characterized by transmission electron microscopy. Figure 3The TEM image of PEI (a) shows that PEI has a layered structure and presents a typical polymer morphology; and the SEM image (d) shows that 1-PyCA:PEI forms a film. Further observation of the TEM images with a scale of 20nm (b) and 5nm (c) shows that the 1-PyCA-PEI film clearly shows lattice fringes with a spacing of about 0.34nm, which corresponds to the (002) plane spacing of graphite, indicating that the two components may combine to form graphite crystallites.

[0065] The elemental composition and chemical structure of 1-PyCA:PEI were further studied using Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy.

[0066] Figure 4 In the FTIR spectrum, PEI is at 3309cm -1 The characteristic absorption peaks detected at 2938 and 2818 cm are attributed to the NH stretching vibration. -1 The characteristic peak at 1597 cm is attributed to its CH stretching vibration. -1 The C=C stretching vibration at 3038cm -1 The CH stretching vibration at 3309 cm-1 of 1-PyCA:PEI is a typical feature of the aromatic ring in 1-PyCA. -1 and 2938cm -1 The characteristic NH and CH stretching vibrations of PEI were observed at 1375 cm -1 and 1313cm -1 The CN and NH stretching vibration peaks are shown at 1670 cm -1 and 1558cm -1 There are two peaks at 1670 cm -1 The peak at 1558cm is due to the carbonyl group of carboxylic acid, while the peak at 1558cm -1 The peak at was assigned to the amide carbonyl group. These findings suggest that an amidation process occurred between 1-PyCA and PEI, resulting in the effective grafting of 1-PyCA onto PEI.

[0067] and then, Figure 5Two prominent peaks were observed in the XPS spectrum of 1-PyCA:PEI: C1s peak at 284.8eV and N1s peak at 400.2eV. Further high-resolution C1s spectrum showed two different peaks at 284.7 and 288.2eV, of which the peak at 284.7eV was attributed to CC / C=C (graphitic carbon), indicating the presence of a highly conjugated carbon structure in 1-PyCA:PEI; the peak at 288.2eV indicated the presence of O=C / O=CN, further proving the amidation reaction between 1-PyCA and PEI. The N1s peak in 1-PyCA:PEI can be fitted into two characteristic peaks, corresponding to pyrrolic nitrogen (399.1eV) and graphitic nitrogen (400.8eV), respectively. The ratios of pyrrolic nitrogen and graphitic nitrogen in PEI were 92.5% and 7.5%, respectively, while in 1-PyCA:PEI, the ratios became 97.15% and 2.85%; the increase in pyrrolic nitrogen content was attributed to the amidation reaction between 1-PyCA and PEI, further proving that an intermolecular reaction occurred between the two components; compared with the N1s peak of PEI (398.45 eV and 399.25 eV), the N1s peak of 1-PyCA:PEI shifted to higher binding energy values ​​at 399.1 eV and 400.8 eV, which was due to the interaction between 1-PyCA and PEI, the electron cloud density of nitrogen atoms in PEI decreased, and the amino group transferred charge to 1-PyCA.

[0068] Example 6

[0069] Weigh 0.12 g of 1-pyrenecarboxylic acid, dissolve it in 30 mL of ethanol, and disperse it ultrasonically for 30 min. Add 7.5 mL of 8 mg / mL PEI ethanol solution, transfer it to a high-pressure reactor, and heat it to 120°C for solvothermal reaction for 15 h.

[0070] After the reaction was completed, the mixture was naturally cooled to room temperature, and the reaction solution was taken out to prepare a 1-PyCA:PEI ethanol solution with a mass ratio of 1-PyCA to PEI of 1:0.5. The ethanol solution was directly used as the ETL material of OSCs.

[0071] Example 7

[0072] Weigh 0.12 g of 1-pyrenecarboxylic acid, dissolve it in 30 mL of ethanol, and disperse it ultrasonically for 30 min. Add 12 mL of 8 mg / mL PEI ethanol solution, transfer it to a high-pressure reactor, and heat it to 150° C. for solvothermal reaction for 15 h.

[0073] After the reaction was completed, the mixture was naturally cooled to room temperature, and the reaction solution was taken out to prepare a 1-PyCA:PEI ethanol solution with a mass ratio of 1-PyCA to PEI of 1:0.8. The ethanol solution was directly used as the ETL material of OSCs.

[0074] Example 8

[0075] Weigh 0.12 g of 1-pyrenecarboxylic acid, dissolve it in 30 mL of ethanol, and disperse it by ultrasonic for 30 min. Add 15 mL of 8 mg / mL PEI ethanol solution, transfer it to a high-pressure reactor, and heat it to 200 °C for solvent thermal reaction for 15 h.

[0076] After the reaction was completed, the mixture was naturally cooled to room temperature, and the reaction solution was taken out to prepare a 1-PyCA:PEI ethanol solution with a mass ratio of 1-PyCA to PEI of 1:1. The ethanol solution was directly used as the ETL material of OSCs.

[0077] Example 9

[0078] In order to further verify the electrical properties of the ETL material prepared by the present invention, different material films were used as ETL layers to prepare single electron layer devices with a structure of ITO / ETL / Al for testing. Figure 6 The IV curve of the single-electron layer device is shown.

[0079] The direct current (DC) conductivity (σ0) of different ETL material films can be directly estimated by the following formula:

[0080] In the formula, d is the thickness of the electron transport layer film (30nm), A is the effective area of ​​the battery (0.045 cm 2 ).

[0081] According to the formula, the conductivity of the original ZnO, PEI, and Pyrene:PEI films are 5.36×10 -4 ,7.59×10 -8 , 1.05×10 -4 S m -1 .

[0082] The results show that the conductivity of the Pyrene:PEI material film prepared by the present invention is greatly improved compared with the PEI film, which indicates that the electron mobility of the ETL material of the present invention is also greatly improved.

[0083] Example 10

[0084] The Pyrene:PEI (1:0.2) ethanol solution prepared in Example 1 was used as the ETL material to prepare a device structure of ITO / Pyrene:PEI / PM6:BO-4Cl:PC 61 OSCs of BM / MoO3 / Al.

[0085] The OSCs have a six-layer structure, in which the first layer is a conductive light-transmitting glass layer, the second layer is an ITO layer, the third layer is an ETL, namely Pyrene:PEI, and the fourth layer is an organic active layer, namely PM6:BO-4Cl:PC 61 BM, the fifth layer is HTL, i.e. MoO3, and the sixth layer is Al electrode. The preparation processes of OSCs are all traditional processes without special requirements.

[0086] An ITO glass with a size of 298 mm × 1 mm × 198 mm was placed on a polytetrafluoroethylene support and placed in deionized water, anhydrous ethanol, acetone, and isopropanol in sequence for ultrasonic cleaning.

[0087] The cleaned ITO glass was placed in a 60°C oven to remove the isopropanol solution remaining on the surface, and then placed in a closed UV irradiation box and irradiated for 30 minutes at an irradiation power of 50W.

[0088] Place the ITO glass on a spin coater, drop 0.1 mL of Pyrene:PEI ethanol solution, seal, turn on the spin coater and turn on the vacuum pump to make the vacuum degree in the spin coater reach 2 Pa, and spin coat at a speed of 4500 rpm for 60 seconds. After the spin coating is completed, place the ITO glass on a pre-opened hot stage, anneal at 60°C for 7 minutes, and spin coat the ETL layer on the ITO glass.

[0089] Weigh PM6:BO-4Cl:PC with a mass ratio of 1:1:0.2 61 BM was dissolved in chloroform and stirred at 30°C for 1 h to obtain an active layer solution. 10 min before spin coating the active layer, DIO accounting for 0.5 vol% of the total volume of the solvent was added to the active layer solution and dropped onto the ITO glass on which the ETL layer was spin coated. The active layer was spin coated at 3000 rpm to form a film, and thermally annealed at 100°C for 10 min to obtain an organic active layer.

[0090] Then place the ITO glass with the organic active layer on the top turntable of the vacuum evaporator, weigh 1g of molybdenum oxide and place it on the target platform at the bottom of the vacuum evaporator. Close the vacuum evaporator, turn on the mechanical pump, wait until the pressure in the evaporator drops to 0Pa, turn on the molecular pump, and drop the pressure in the instrument to 2.5×10 -4 Pa, turn on the top turntable of the vacuum evaporator and rotate it at a rate of 15 rpm, turn on the bottom heater of the vacuum evaporator, and start evaporating molybdenum oxide when the temperature is constant at 350°C, and the evaporation time is 15 min.

[0091] Turn off the bottom heating device and top rotating device of the vacuum evaporator, turn on the vacuum evaporator, place 1g of aluminum on the target platform at the bottom of the vacuum evaporator, repeat the above operation, turn on the bottom heating device of the vacuum evaporator, and start evaporating aluminum when the temperature is constant at 900℃. The evaporation time is 20min, and then turn off the evaporator.

[0092] The ITO glass was taken out from the evaporator to prepare OSCs V1.

[0093] Embodiment 11

[0094] Except for using the Pyrene:PEI (1:0.5) ethanol solution prepared in Example 2, the rest is the same as Example 10, and the device structure prepared is ITO / Pyrene:PEI / PM6:BO-4Cl:PC 61 OSCs V2 of BM / MoO3 / Al.

[0095] Example 12

[0096] Except for using the Pyrene:PEI (1:0.8) ethanol solution prepared in Example 3, the rest is the same as Example 10, and the device structure prepared is ITO / Pyrene:PEI / PM6:BO-4Cl:PC 61 OSCs V3 of BM / MoO3 / Al.

[0097] Example 13

[0098] Except for using the Pyrene:PEI (1:1) ethanol solution prepared in Example 4, the rest is the same as Example 10, and the device structure prepared is ITO / Pyrene:PEI / PM6:BO-4Cl:PC 61 OSCs V4 of BM / MoO3 / Al.

[0099] Embodiment 14

[0100] The same method as in Example 10 was used except that the 1-PyCA:PEI (1:0.2) ethanol solution prepared in Example 5 was used. The device structure was ITO / 1-PyCA:PEI / PM6:BO-4Cl:PC 61 OSCs V5 of BM / MoO3 / Al.

[0101] Embodiment 15

[0102] Except for using the 1-PyCA:PEI (1:0.5) ethanol solution prepared in Example 6, the rest is the same as Example 10, and the device structure prepared is ITO / 1-PyCA:PEI / PM6:BO-4Cl:PC 61 OSCs V6 of BM / MoO3 / Al.

[0103] Example 16

[0104] The same method as in Example 10 was used except that the 1-PyCA:PEI (1:0.8) ethanol solution prepared in Example 7 was used. The device structure was ITO / 1-PyCA:PEI / PM6:BO-4Cl:PC 61 OSCs V7 of BM / MoO3 / Al.

[0105] Embodiment 17

[0106] Except for using the 1-PyCA:PEI (1:1) ethanol solution prepared in Example 8, the rest is the same as in Example 10, and the device structure prepared is ITO / 1-PyCA:PEI / PM6:BO-4Cl:PC 61 OSCs V8 of BM / MoO3 / Al.

[0107] Comparative Example 1

[0108] A PEI ethanol solution with a concentration of 8 mg / mL was directly used as the ETL material of OSCs. According to the preparation method in Example 10, a device structure of ITO / PEI / PM6:BO-4Cl:PC was prepared. 61 OSCs V9 of BM / MoO3 / Al.

[0109] Comparative Example 2

[0110] The same method as in Example 10 was used except that the Pyrene:PEI (1:0.8) ethanol solution prepared in Example 3 was used and the annealing temperature was changed to 200°C. The device structure prepared was ITO / Pyrene:PEI / PM6:BO-4Cl:PC 61 OSCsV10 of BM / MoO3 / Al.

[0111] Comparative Example 3

[0112] Sol-gel ZnO was used as the ETL layer material, and the device structure was prepared according to the conventional preparation method: ITO / ZnO / PM6:BO-4Cl:PC 61 BM / MoO3 / Al OSCs V11, where the annealing temperature of the ZnO layer is set to 200℃.

[0113] Comparative Example 4

[0114] Sol-gel ZnO was used as the ETL layer material, and the device structure was prepared according to the conventional preparation method: ITO / ZnO / PM6:BO-4Cl:PC 61 BM / MoO3 / Al OSCs V12, where the annealing temperature of the ZnO layer is set to 60℃.

[0115] Application Example 1

[0116] Taking the OSCs prepared in Example 12 and Comparative Example 1 as examples, the electrochemical properties of the devices were tested.

[0117] from Figure 7 of JV The curve shows that the performance of Pyrene:PEI-based devices is significantly better than that of PEI-based devices. Figure 8 The EQE spectrum also shows that Pyrene:PEI-based devices exhibit higher light absorption in the entire light response wavelength range of 300 to 1000 nm.

[0118] Furthermore, by comparing the EQE spectrum calibration J SC (26.57mA cm -2 ), and from JV The measured value of 26.68 mA cm -2 of J SC The results are basically consistent, with a deviation of less than 5%.

[0119] Application Example 2

[0120] In order to further explore the influence of different ETL materials on the exciton dissociation and charge transport of the device, the dark state of organic solar cells with PEI and Pyrene:PEI as the electron transport layer was tested and analyzed by Example 12 and Comparative Example 1. JV curve.

[0121] The specific fitting curve is as follows Fig. 9 The results show that the leakage current density of the Pyrene:PEI device is close to that of the PEI device at -2 to 0 V, but the dark state of the Pyrene:PEI device is JV The curve has a higher on-state voltage within the range of 0 to 2 V, indicating that it has a higher rectification ratio and a better diode effect.

[0122] Dark State JV The curve can be described by the following formula:

[0123] in, J 0. q , n , R s , R sh , k B , T and J PHThey are dark state reverse saturation current density, elementary charge, diode ideality factor, series resistance, shunt resistance, Boltzmann constant, absolute temperature and photogenerated current density.

[0124] In the dark, assuming the photocurrent density is 0 ( J PH =0), the key performance parameters of different ETL materials can be fitted according to the above formula and are listed in Table 1.

[0125]

[0126] According to the devices in Table 1 R sh and R s It can be seen that the Pyrene:PEI device R s Significantly reduced, R sh The results show that Pyrene:PEI can reduce charge recombination to varying degrees, promote charge extraction, and form ohmic contact between the active layer and the cathode interface layer, which is consistent with the higher FF and J SC The Pyrene:PEI device has a lower J 0 indicates that its electron injection and hole blocking performances are better.

[0127] For an ideal diode with only diffusion current at the junction, n = 1, for nodes where the composite is dominant, n will be close to 2. Therefore, the n The smaller the value, the smaller the charge recombination at the interface. According to the data in Table 1, it can be concluded that the use of Pyrene:PEI reduces the charge recombination at the interface and increases the carrier selectivity.

[0128] Application Example 3

[0129] Table 2 gives in detail the performance statistical results of the OSCs devices prepared in Examples 10 to 17 of the present invention and Comparative Examples 1 to 4.

[0130]

[0131] Among them, the photoelectric conversion efficiency (PCE) of the OSCs device V9 prepared with PEI as the ETL material is only 8.38%, while the PCE of the OSCs device prepared with PEI modified by the polycyclic aromatic hydrocarbons or their derivatives as the ETL material involved in the present invention is significantly better than that of PEI-based OSCs.

[0132] In particular, the device V3 with Pyrene:PEI (1:0.8) as the ETL material showed an optimal PCE of 15.91%, proving that the modification of PEI with polycyclic aromatic hydrocarbons or their derivatives has a significant promoting effect on improving the conductivity of PEI. The various properties of OSCs devices can be greatly improved, including the short-circuit current density (Short-Circuit CurrentDensity, J SC ) and fill factor (FF) have been significantly improved.

[0133] Furthermore, by comparing V3 and V10, it can be found that the Pyrene:PEI material prepared by the present invention still has a PCE of 77% of the optimal device under annealing conditions at 200°C, showing its certain heat resistance.

[0134] By comparing V3 with V11, it is found that the performance of the Pyrene:PEI-based device prepared by the present invention is even better than that of the ZnO-based device, which further demonstrates the potential of the Pyrene:PEI material. In contrast to V3 and V12, the ZnO material annealed at 60°C no longer has the ability to transport charges, which further demonstrates the low-temperature superiority of the Pyrene:PEI material prepared by the present invention.

[0135] Application Example 4

[0136] In order to study the interface impedance changes of devices with different electron transport layers, the electrochemical impedance spectroscopy (EIS) of OSCs based on different ETLs in Example 12 and Comparative Example 1 was tested, and the results were obtained. Fig.10 The Nyquist diagram shown.

[0137] In the figure, the interfacial impedance of PEI-based OSCs (53Ω) is significantly higher than that of Pyrene:PEI-based 634Ω. This is mainly because the low electron mobility of PEI seriously hinders the charge transfer at the electrode interface. The interfacial impedance of organic solar cells with Pyrene:PEI as the electron transport layer is greatly reduced, which further shows that the conductivity of Pyrene:PEI composite materials is greatly improved compared with PEI, and the defects at the interface are reduced, which is conducive to good charge transfer and collection at the interface, which is consistent with the conductivity test results.

[0138] Application Example 5

[0139] In order to verify the use stability of the OSCs device prepared by the present invention, air stability and UV stability tests were carried out on the OSCs devices prepared in Example 12 and Comparative Example 1, respectively.

[0140] In the air stability test, the device was exposed to air at a temperature of 18°C ​​and a humidity of 5% for 135 hours without any packaging. The results are as follows: Fig.11 As shown, the device of Example 12 can still maintain about 97% of the initial photoelectric conversion efficiency, while the photoelectric conversion efficiency of the device of Comparative Example 1 is only 91% of its initial photoelectric conversion efficiency.

[0141] The stability of the device under strong ultraviolet light (365nm, 150mW / cm²) was further tested. After 100h of ultraviolet light irradiation, Fig.12 The Pyrene:PEI-based device of Example 12 can still maintain about 68% of the initial efficiency, while the photoelectric conversion efficiency of the PEI-based device of Comparative Example 1 has dropped to about 35% of the initial efficiency after only 20 hours of UV irradiation, thereby demonstrating the superior UV stability of the device of the present invention.

[0142] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.

Claims

1. A highly conductive polymer transport layer material, which is a material composed of an imine polymer as a base material and a polycyclic aromatic hydrocarbon or a derivative thereof grafted onto its molecular side chain by a solvent thermal reaction, wherein the imine polymer is any one of PEI, PEIE, PDINN, or a halogen element substituted derivative thereof, and the polycyclic aromatic hydrocarbon or a derivative thereof is naphthalene, phenanthrene, anthracene, pyrene, or a small molecule substituted derivative thereof as the core.

2. The highly conductive polymer transmission layer material according to claim 1, characterized in that The small molecule substituted derivative is a carboxylic acid substituted derivative.

3. The highly conductive polymer transmission layer material according to claim 2, characterized in that The carboxylic acid substituted derivative is 1-naphthoic acid, 2-naphthoic acid, 9-anthracenecarboxylic acid or 1-pyrenecarboxylic acid.

4. The highly conductive polymer transmission layer material according to claim 1, 2 or 3, characterized in that The mass ratio of the imine polymer to the polycyclic aromatic hydrocarbon or its derivative is (0.2-1):

1.

5. The method for preparing the highly conductive polymer transport layer material according to claim 1 is to dissolve a polycyclic condensed aromatic hydrocarbon or its derivative in an alcohol solvent, add the alcohol solution of the imine polymer according to a mass ratio of the imine polymer to the polycyclic condensed aromatic hydrocarbon or its derivative of (0.2 to 1):1, carry out a solvent thermal reaction at 100 to 200° C. in a sealed container, and directly use the alcohol solution of the reaction product as the ETL material.

6. The method for preparing a highly conductive polymer transmission layer material according to claim 5, characterized in that The solvent thermal reaction time is 10 to 15 hours.

7. Use of the highly conductive polymer transport layer material of claim 1 as an ETL material for OSCs.

8. The use according to claim 7 is to spin-coat the material according to claim 1 on a conductive substrate, and then perform annealing to form an ETL layer on the surface of the conductive substrate.

9. The use according to claim 8, characterized in that The annealing temperature of the ETL material is 60°C.

10. An organic solar cell using the highly conductive polymer transport layer material of claim 1, comprising spin coating the material of claim 1 on a conductive substrate to form an ETL layer, and then spin coating an organic active layer, vacuum evaporating a HTL layer and a metal electrode.

Citation Information

Patent Citations

  • Near-infrared carbon dots as well as preparation method and application thereof

    CN114921245A

  • Organic solar cell based on hybrid cathode interface layer and preparation method thereof

    CN115275014A

  • Method for inducing perovskite thin film crystallization through carbon dots and perovskite light-emitting diode

    CN115440920A

  • Fluorine-containing polymer, preparation method thereof and perovskite solar cell

    CN117229503A

  • Organic Photoactive Layer Composite Ink, Organic Solar Cell and Preparation Methods Thereof

    US20190393423A1